Physiological bases of genetic gains in sugarcane yield in Argentina - Acreche, Martin Moises; Saez, Julio Victor; Chalco Vera, Jorge Elias (Elsevier, 2018)
Breeding and management efforts during the 20th century have increased sugar yield in almost all sugarcane areas worldwide. However, a close analysis of the trends during the last decades reveals that the rate of increase in sugar yield has been actually slowing down since the 1980s. An experiment was conducted to compare sugarcane varieties representing different eras of genetic improvement in Argentina (one widely grown self-pollination variety, 11 released sugarcane hybrids and one advanced breeding hybrid) during the 2010/11, 2011/12 and 2012/13 growing seasons under rainfed field conditions in Tucumán, the main sugarcane area of Argentina. The aim of the experiment was to quantify the achievements in sugarcane breeding since 1940 in Tucumán, by identifying the main crop physiological bases responsible for yield increases. Genetic gains for sugar yield were 0.08 and 0.14 Mg ha−1 y−1 for plant and ratoon cane, respectively. There was a linear increase in sugar yield, cane yield, sugar content and average stem weight with the year of release of the varieties throughout the period from 1940 to 2010. The increase in sugar yield was linearly and positively related to cane yield, sugar content and average stem weight, whereas the increase in cane yield was associated to average stem weight and not to the number of stems. Breeding also increased the total above ground dry biomass and the dry stem weight. However, the partitioning of total above ground dry biomass to stems or to sugar were not increased by breeding. These findings reveal that the varieties continuously released by Argentine sugarcane breeding programs have not reached a “plateau” in sugar yield.